2021
DOI: 10.3390/cells10102719
|View full text |Cite
|
Sign up to set email alerts
|

Cycloastragenol, a Triterpenoid Saponin, Regulates Oxidative Stress, Neurotrophic Dysfunctions, Neuroinflammation and Apoptotic Cell Death in Neurodegenerative Conditions

Abstract: Here, we have unveiled the effects of cycloastragenol against Aβ (Amyloid-beta)-induced oxidative stress, neurogenic dysfunction, activated mitogen-activated protein (MAP) kinases, and mitochondrial apoptosis in an Aβ-induced mouse model of Alzheimer’s disease (AD). The Aβ-induced mouse model was developed by the stereotaxic injection of amyloid-beta (5 μg/mouse/intracerebroventricular), and cycloastragenol was given at a dose of 20 mg/kg/day/p.o for 6 weeks daily. For the biochemical analysis, we used immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…These results have proven that AS-IV prevents Aβ-induced apoptosis of SK-N-SH cells by suppressing the opening of mPTP, the production of intracellular ROS, and increasing the level of anti-apoptosis molecules ( Sun et al, 2014 ). In vivo study by Ikram et al (2021) showed similar results. Increased oxidative stress was observed in Aβ injected mice, accompanied by significant neuronal loss and increased levels of Bax, casp-3, and Bim.…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...supporting
confidence: 63%
See 1 more Smart Citation
“…These results have proven that AS-IV prevents Aβ-induced apoptosis of SK-N-SH cells by suppressing the opening of mPTP, the production of intracellular ROS, and increasing the level of anti-apoptosis molecules ( Sun et al, 2014 ). In vivo study by Ikram et al (2021) showed similar results. Increased oxidative stress was observed in Aβ injected mice, accompanied by significant neuronal loss and increased levels of Bax, casp-3, and Bim.…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...supporting
confidence: 63%
“…These data suggest that the PPARγ signaling pathway is the key target of AS-IV in suppressing the inflammatory reaction as well as other molecular changes in the hippocampus. In another study by Ikram et al (2021) , Aβ was stereotaxically injected into the lateral ventricle of mice to induce the Alzheimer’s disease model, followed by 6 weeks treatment of cycloastragenol, a triterpenoid saponin present in AR. It was found that Aβ injection reduced the number of neurons, levels of BDNF, phosphorylated receptor tropomyosin receptor kinase B (p-TrKB), nuclear factor erythroid 2-related factor 2 (Nrf-2), hemo oxygenase-1 (HO-1), and increased oxidative stress markers, which might be mediated by the MAP kinases (MAPK) as expression levels of p-JNK, p-P-38, p-Erk were increased.…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...mentioning
confidence: 99%
“…However, synthetic antioxidants have shown a potential toxicity risk and their applications are strictly regulated [ 13 , 14 ]. Therefore, researchers are focusing their research interests on natural active molecules and their derivatives, such as flavonoids, triterpenoid, quinones, and alkaloids [ 12 , 15 , 16 , 17 ]. Remarkably, antioxidant peptide (AP) originated from food proteins, which captured worldwide interest because of their advantages in environmental protection and in sustainability, and their small molecular weight (MW) and low toxic side effects [ 1 , 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are several studies describing CA as a neuroprotective compound against several neurotoxic agents such as Aβ1-42 peptide (Ikram et al, 2021) and 6-OHDA (6-hydroxydopamine) (Nesil et al, 2011). As our data clearly revealed that CA increased Nrf-2, telomerase, and proteasome activity, which reportedly alleviate neurotoxicity, CA-mediated protection against 6-OHDA was next investigated in the context of the involvement of Nrf-2 and hTERT.…”
Section: Resultsmentioning
confidence: 99%